Elevated des-Angi-angiotensinogen levels by nephrectomy and adrenalectomy - Hilgenfeldt, Ulrich; Schwind, Sylvia; Muley, Thomas; Rubin, Inger (Clinical and experimental hypertension, 1996)
This study investigates the time course of plasma levels of angiotensinogen (Aogen) and of the Aogen metabolite des-Angl-angiotensinogen (des-Angl-Aogen) in nephrectomized rats with and without adrenals for 24 h. After nephrectomy the plasma Aogen levels increase 5-fold over the following 24 h. The increase is significantly lower after sham nephrectomy (3.7-fold, P<0.05) and if the kidneys are withdrawn without decapsulization (2.4-fold, P<0.05). A small and transient increase arise after nephrectomy plus adrenalectomy (1.6-fold after 8h, P<0.005). After adrenalectomy alone Aogen levels continuously shrink to 38% of control values after 24h. Plasma des-Angl-Aogen levels increase 2.1- to 3.7-fold 24h after the different nephrectomy procedures. In connection with recent findings these data support the notion that the increase in Aogen plasma levels after bilateral nephrectomy is triggered by renin, released during surgery. High plasma levels of des-Angl-Aogen after nephrectomy indicate that AngI is generated by tissue renin, e.g., in the adrenals. This suggests that after nephrectomy the plasma des-Angl-Aogen levels should be a valuable proof for the evaluation of the amount of generated angiotensin. This paper has partly been presented in the 14th scientific meeting of the International Society of Hypertension, Madrid, 1992.
Elektronische Reproduktion der Druck-Ausgabe 3. Juli 2009
Gesehen am 10.11.2025